Initiating end-of-life care pathways: a discussion paper - Tessa Watts (Journal of Advanced Nursing, 2012)
This theoretical paper critically examines the decision making challenges associated with the initiation of an end of life care pathway such as the Liverpool Care Pathway. Four particular chalenges are identified and discussed, namely, marking the transition to terminal care, dealing with ambiguity, reaching professional consensus and engaging patients and families in decision-making.